(untitled) (Research, Society and Development, 2020)
Non-steroidal anti-inflammatory drugs (NSAIDs), being freely marketed, are among the most prescribed drugs in the world, have anti-inflammatory, analgesic and antipyretic action by inhibiting prostaglandins by blocking cycloxygenases (COX). Currently, it is known that there are three COX enzymes with different actions. It has been postulated that the pharmacological properties of NSAIDs stem mainly from the inhibitory action of COX-2, while adverse reactions are the result of COX-1 inhibition, creating subgroups of NSAIDs: preferential, selective and non-selective for COX-2. The introduction of COX-2 inhibitors in clinical practice aims to maintain anti-inflammatory efficacy without undesirable adverse effects. However, studies suggest toxicity associated with its use. The objective of this word is to gather information about the side effects of the prolonged use of NSAIDs that inhibit COX-2 in the equine species. For this, a bibliographic review was carried out looking for studies on the effects of the use of COX-2 inhibitors in horses. It was observed that this class of drugs has several toxic effects for the species, mainly in situations where there have been overdoses, prolonged use and association with other NSAIDs. Control measures are needed in the commercialization of these drugs. The choice of drug for treatment must be individualized for each patient, taking into account their risk factors and benefits. Its rational use is an important ally of veterinary clinicians in promoting animal health and well-being.